Neisseria Gonorrhoeae Pilus Attenuates Cytokine Response of Human Fallopian Tube Explants - Cardenas-Sankan, G; Orihuela-Diaz, P; Velasquez, L (2012)
Background. A role for pilus during attachment of Neisseria gonorrhoeae to epithelia of the female reproductive tract is currently assumed. However, Pil - gonococci have been observed during infection of the reproductive tract, which prompted us to examine the effect of pili on the dynamics of infection and the inflammatory responses of mucosal explants of the human Fallopian tube. Methods. Mucosal explants were infected in vitro with Opa negative Pil - and Pil + N. gonorrhoeae strains. Results. Piliation enhanced gonococcal adherence to the epithelium within 3h of infection (P<0.05) but thereafter did not offer advantage to gonococci to colonize the epithelial cell surface (P>0.05). No differences were found between the strains in numbers of gonococci inside epithelial cells. Pil - bacteria induced higher levels (P<0.05) of IL-1?, TNF-?, GM-CSF, MCP-1, and MIP-1? than Pil + bacteria. There were no differences between both strains in LOS pattern, and Pil expression did not change after coincubation with mucosal strips. Conclusions. Results show that gonococcal invasion of the human Fallopian tube can occur independently of pilus or Opa expression, and suggest that pilus, by inhibition of several key elements of the initial inflammatory response, facilitates sustained infection of this organ. Copyright 2012 Luis Velasquez et al.